Government subsidies' influence on corporate social responsibility of private firms in a competitive environment - Wenqi Duan; Adnan Khurshid; Abdur Rauf; Adrian Cantemir Calin (Journal of Innovation & Knowledge (JIK), 2022)
Corporate involvement with social responsibility (CSR) is a voluntary practice. However, governments have recently adopted a more supportive stance by providing research and development support and tax exemptions. Therefore, this study examines the role of government subsidies (Sub) in CSR, considering the amount and number of subsidies and the type of industry in a competitive business environment. The paper establishes theoretical linkages through the construction of an oligopolistic market model of private enterprises based on industrial organisation theory's structure-conduct-performance (SCP) paradigm. Moreover, our study tests the empirical relationship using a dataset of 100 listed companies in Pakistan observed from 2011 to 2019 using robust standard error methodologies and a fixed effects IV estimator. The results show that government subsidies significantly promote private enterprises to actively fulfil their social responsibilities, and product market competition plays an intermediary role that endorses the theoretical proposition. This effect is visible at all stages of the enterprise's life cycle. Additionally, the relationship is more prominent in the case of low- and medium-sized government subsidies, competitive industries, and firms with no political connections. The results further reveal that product market competition is the primary channel through which government subsidies influence CSR. Concurrently, optimising the allocation of financial resources has specific significance.
Keywords: M14; H25; L13; 650; Corporate social responsibility; Government subsidies; Oligopoly market model; Private enterprises; Product market competition